GAMBARAN PENGETAHUAN IBU TENTANG PENCEGAHAN RUAM POPOK PADA BAYI USIA 0 – 12 BULAN DI WILAYAH KERJA PUSKESMAS TANJUNG SENGKUANG KOTA BATAM - Frisca Anjani, Melita; Mariyana; Abd Hafid, Rachmawati (Universitas Batam, 2025)
Currently, the use of disposable diapers is widely used by mothers who have babies aged 0- 12 months. Based on the Indonesian Pediatric Association (IDAI) suggests the use of diapers should be changed every 2 - 3 hours. Because anatomically and physiologically the baby's skin is relatively thin, delicate, the pH of the skin is acidic, and the inner layer has higher humidity. Baby's skin is often exposed to urine or feces for a long time, potentially causing skin irritation. Skin irritation that often occurs in infants is diaper rash. One of the efforts that can be made to prevent diaper rash is perinatal care. The purpose of this study was to determine the level of knowledge and behavior of mothers regarding the prevention of diaper rash in infants aged 0-12 months. This study used a questionnaire consisting of two parts, namely a knowledge questionnaire. The research design used a descriptive survey. The population in this study were mothers who had babies in the working area of Tanjung Sengkuang Community Health Center, Batam City in 2024, totaling1801 people, while the number of samples was 30 mothers, with the sampling technique being accidental sampling. The results of univariate analysis showed that the level of knowledge of mothers about diaper rash was good Keywords: Diaper rash, baby, mother